A Framework for Systematic Design and Operation of Condition-Based Maintenance Systems: Evidence from a Case Study of Fleet Management at Sea Ports - Lewandowski, Marco; Scholz-Reiter, Bernd (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Ongoing improvement of logistics and intermodal transport leads to high requirements regarding availability of machine resources like straddle carriers or gantry cranes. Accordingly, efficient maintenance strategies for port equipment have to be established. The change to condition-based maintenance strategies promises to save resources while enhancing availability and reliability. This paper introduces a framework of methods and tools that enable the systematic design of condition-based maintenance systems on the one hand and offers integrated support for operating such systems on the other hand. The findings are evaluated based on a case-study of a German seaport and illustrate the usage of the system based on managing the equipping process of machines with sensors for condition monitoring as well as bringing the system into the operation phase.